Growth and trends of pigeonpea (Cajanus cajan) in Uttar Pradesh state - RANI, REKHA; UDGATA, ASHIS RANJAN; KUMAR, HEMANT; DEVRAJ; SAH, UMA; DIXIT, GIRISH PRASAD (The Indian Journal of Agricultural Sciences, 2025)
The present study evaluated the growth performance of area, production and yield of pigeonpea (Cajanus cajan L. Millsp.) in different districts as well as agroclimatic zones of Uttar Pradesh. The study used time series data of 25 years i.e. from 1997–98 to 2022–23. Emphasising the role of National Food Security Mission (NFSM) on pulses production, the entire study period was divided into two sub-periods; sub-period I: 1997–98 to 2007–08 (Pre NFSM) and sub-period II: 2007–08 to 2022–23 (Post NFSM). Compound annual growth rate was used to study the growth rate in area, production and yield for all the districts. Among the agroclimatic zones, Bundelkhand zone and Vindhyan zone were found to be efficient zones showing positive growth rate in area and production. Further in post NFSM period, majority of the districts were observed to be showing positive growth rate in yield which can be attributed to the enhanced input supply and advanced technologies introduced through this programme. The pre and post NFSM comparative analysis clearly depicted the role of improved production technologies and knowledge dissemination through extension activities under programme in the improved pigeonpea production scenario in different agroclimatic zones of Uttar Pradesh. Being among the major pigeonpea producing states, targeted policy interventions under various programmes should focus on districts showing high yield growth rates for maximising production of the state, paving towards achieving pulse self-sufficiency in India.